(untitled) (Mongolian Journal of International Affairs, 2025)
The strategic significance of People’s Republic of Mongolia during World War II has long occupied a marginal position in Chinese academic research concerning the history of war and regional politics. The existing literature on this subject is characterized by a lack of independence and systematicity in analysis. This paper utilizes a systematic approach to reviewing and analyzing extant Chinese academic literature to establish a link between the overall structure and the detailed research. It also assesses how Chinese academics recognize the functional role of People’s Republic of Mongolia in the Soviet Union’s military-strategic system, starting from three representative wartime scenarios. First, in the Battle of Khalkhin Gol, although People’s Republic of Mongolia was not the main attacking force, it provided key support at the level of tactical coordination and strategic pivot. Secondly, within the context of the wartime material and personnel support system, People’s Republic of Mongolia established a logistical support system encompassing material resources, financial logistics, human capital, and institutionalized assistance. This system functioned as a critical component for the Soviet military to sustain its combat depth. In the North Chahar Campaign, People’s Republic of Mongolia’s military forces exhibited notable mobility and efficiency in their coordinated advancement. This paper posits that, despite the preliminary findings in the research on the role of People’s Republic of Mongolia in Chinese academia, there are deficiencies in the sources of historical materials, analytical perspectives, and regional subjectivity awareness. In light of these limitations, this paper attempts to propose a systematic research framework to promote the advancement of the study of the strategic role of People’s Republic of Mongolia in World War II.